What makes music relaxing? An investigation into musical elements. (May 2020) - Hernandez-Ruiz, Eugenia; James, Bianca; Noll, Jordan; Chrysikou, Evangelia G.
Research on specific qualities of music used for relaxation has shown conflicting results. The use of different familiar or pre-composed pieces, with many simultaneous changes, might limit the ability to discriminate which musical element is responsible for the relaxation response. To address the latter, we examined the relaxing effects of music on three psychophysiological measures (heart rate, respiration rate, and skin conductance) with one original piece of music, and three modified versions (altering one musical element in each version). We investigated whether participants' psychophysiological responses reflected a more "relaxed" state (lower heart rate, respiration rate, and skin conductance) with slower tempo (45 bpm), mellow timbre (bass clarinet), or smaller amplitude (-10 dB). We also investigated whether psychophysiological responses were consistent with self-report scores. Visual inspection of psychophysiological data indicated two distinct responder profiles, and a logistic regression confirmed this distinction. Using mixed ANCOVAs, we found significant differences between participants (responders and non-responders) in skin conductance level. No correlations between psychophysiological measures and self-reports were found. These findings raise interesting questions regarding the mechanisms behind the relaxing effects of music.